The Impact of Pandemic Covid 19 on The Economy in Situbondo - Yahya Arief, Mohammad (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2020)
This study aims to examine the projected impact of Covid-19 in the second quarter of 2020. By using qualitative literature data sourced from secondary data. Situbondo's economic growth projection may not be more than one percent. In general, the agricultural category will grow in the range of minus 3-4 percent. However, it is different with the information and communication category as well as the health service category, the two groups of these categories will enjoy growth above 10 percent.